A method to design mechanical transducers for resonant‐mass gravitational wave detectors. Issue 1 (24th January 2021) - Bortoli, Fabio S.; Frajuca, Carlos; Magalhaes, Nadja S.
Abstract: In this work, a methodology to design two‐mode mechanical transducers for the spherical resonant‐mass gravitational wave detector SCHENBERG is presented. This detector uses microwave multiparametric sensors and has 17 mechanical modes together with 6 electromagnetic modes for the microwave cavities. These transducers, when placed on the spherical surface of the detector, must have an effective mass ratio between their modes constant to provide the better amplification and compose a resonant system that has characteristics necessary for the detection of gravitational waves. To meet this demand, the transducers must form a resonant system with exactly the same quadrupole frequencies of the sphere. This work describes how these transducers were designed using Finite Element Modeling (FEM).